2011
DOI: 10.1097/jom.0b013e318222af67
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy LifeWorks Project

Abstract: Both high-risk reduction and low-risk maintenance are important to contain drug costs. Only low-risk maintenance also avoids absenteeism costs associated with high risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…A third workplace health promotion program that has been demonstrated to have positive effects on employees' health and the organization's health is the comprehensive workplace wellness program in the Department of Justice in Nova Scotia, Canada. As Makrides et al (2011) reported, this program was voluntary and included an annual health risk assessment, competitions among employees to improve their health, incentives, health fairs, and other programs and policies to support healthy behaviors. In an economic analysis, Makrides and colleagues (2011) found that, from 2004 to 2008, employees whose risk scores went from low levels of risk to high levels of risk had the highest increases in both drug costs and absences and that those individuals whose risk scores went down had the lowest increase in drug costs.…”
Section: Systems Approaches To Workplace Wellness Programsmentioning
confidence: 99%
“…A third workplace health promotion program that has been demonstrated to have positive effects on employees' health and the organization's health is the comprehensive workplace wellness program in the Department of Justice in Nova Scotia, Canada. As Makrides et al (2011) reported, this program was voluntary and included an annual health risk assessment, competitions among employees to improve their health, incentives, health fairs, and other programs and policies to support healthy behaviors. In an economic analysis, Makrides and colleagues (2011) found that, from 2004 to 2008, employees whose risk scores went from low levels of risk to high levels of risk had the highest increases in both drug costs and absences and that those individuals whose risk scores went down had the lowest increase in drug costs.…”
Section: Systems Approaches To Workplace Wellness Programsmentioning
confidence: 99%
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Se ha comprobado que los costos por ausentismo laboral son menores (17) cuando se implementan programas de promoción de la salud, ya que estos contribuyen a la merma de factores de riesgo para la salud, lo que incide a su vez en la mengua de los costos de atención por enfermedad (18). Esto facilita ver claramente que existe un impacto positivo en costos para la empresa, siempre y cuando se involucre al trabajador desde la planeación hasta la ejecución, lo cual favorece un ambiente laboral saludable, retomando los fundamentos de la estrategia pslt (19).…”
Section: Condiciones Individualesunclassified